Introducing Petrachlorosaceae fam. nov., Petrachloros gen. nov. and Petrachloros mirabilis sp. nov. (Synechococcales, Cyanobacteria) Isolated from a Portuguese UNESCO monument. Issue 2 (5th March 2022) - Soares, Fabiana; Trovão, João; Ahn, Anne‐Catherine; Wilmotte, Annick; Cardoso, Susana M.; Tiago, Igor; Portugal, António
Abstract : The Synechococcales is a large cyanobacterial order comprising both unicellular and filamentous forms, with parietal thylakoid arrangement. Previously, this order has been the subject of taxonomic revisions with new families being erected. During studies of the phototrophic communities on the limestone walls of the Old Cathedral of Coimbra (UNESCO monument), a coccoid Aphanocapsa ‐like cyanobacterium was isolated. It was characterized using a polyphasic approach, based on morphology, 16S rRNA phylogenetic and phylogenomic analyses, internal transcribed spacer (ITS) secondary structure, and ecology. The 16S rRNA phylogenetic analyses showed that this strain is placed in a separate and highly supported family‐level clade, as part of a large group comprising the families Prochlorococcaceae and Prochlorotrichaceae, with Lagosinema as the closest (although quite distant) taxon. Additionally, the phylogenomic analysis also placed this strain in a separate lineage, situated distantly apart from the family Thermosynechococcaceae, but with strains assigned to Acaryochloris marina MBIC 11017 and Aphanocapsa montana BDHKU210001 as the closest taxa. Based on these data, as well as on the results from the secondary ITS structure, morphology, and ecology, we here propose the establishment of Petrachlorosaceae fam. nov., along with the description of Petrachloros gen. nov. and Petrachloros mirabilis sp. nov. We also address additional considerations regarding some cyanobacterial taxa within the order Synechococcales, which we believe deserve further revisions.